Older adults’ willingness to communicate and emotions in the EFL classroom context: Results of a pilot study - Borkowska, Anna (Neofilolog, 2025)
The main objective of this paper is to examine the relationships among older adults’ in-class willingness to communicate (WTC) in English, enjoyment, and anxiety. The instrument was a questionnaire that comprised biodata items and three adapted scales, namely the WTC in English Scale (Peng, Woodrow, 2010), the Foreign Language Enjoyment (FLE) Scale (Dewaele, MacIntyre, 2014), and the Foreign Language Classroom Anxiety (FLCA) Scale (Horwitz et. al., 1986). The statistical analysis revealed that the participants’ WTC (51 members of the University of the Third Age) was relatively high and there was a moderate, positive relationship between WTC and FLE, as well as a weak, negative correlation between WTC in meaning-focused tasks and FLCA. Also, FLE was very high, which essentially suggested that the respondents’ individual, positive emotions were facilitated in the classroom setting, and positive bonds created in class could be a source of their statistically high social aspect of FLE.